Numerical Modelling Techniques for Marine Debris : A Systematic Literature Review - Subiyanto Subiyanto; Fenyawati Akhmad; Mohammad Fadhli Ahmad; Sudradjat Supian (Research Collaboration Community (RCC), 2023)
Currently, marine debris (MD) is one of them the most worrying global environmental problems because high impact on ecosystems, human health, and economy. One type of MD is that plastics have a significant and growing component, comprising between 60 - 80% of MD globally. Numerical model is an amalgamation of a large number of mathematical equations that rely on computers to find approximate solutions to underlying physical problems. Numerical modeling is key to understanding and determining the source, trajectory and fate of marine plastic debris (MPD). The purpose of this study is to review several methods that have been used in marine debris tracking modeling. The method used in this study is the PRISMA Method and Bibliometric Analysis.